TSRF: A Trust-Aware Secure Routing Framework in Wireless Sensor Networks. (8th January 2014) - Duan, Junqi; Yang, Dong; Zhu, Haoqing; Zhang, Sidong; Zhao, Jing
In recent years, trust-aware routing protocol plays a vital role in security of wireless sensor networks (WSNs), which is one of the most popular network technologies for smart city. However, several key issues in conventional trust-aware routing protocols still remain to be solved, such as the compatibility of trust metric with QoS metrics and the control of overhead produced by trust evaluation procedure. This paper proposes a trust-aware secure routing framework (TSRF) with the characteristics of lightweight and high ability to resist various attacks. To meet the security requirements of routing protocols in WSNs, we first analyze features of common attacks on trust-aware routing schemes. Then, specific trust computation and trust derivation schemes are proposed based on analysis results. Finally, our design uses the combination of trust metric and QoS metrics as routing metrics to present an optimized routing algorithm. We show with the help of simulations that TSRF can achieve both intended security and high efficiency suitable for WSN-based networks.